IMPLEMENTASI PETA STRATEGI DALAM DUNIA PENDIDIKAN DI INDONESIA - Khairul, Agus; Darisman, Encep (Jurnal Ilmiah Pendidikan dan Keislaman, 2022)
A strategy map is a diagram that illustrates the causal relationships between the components of a strategy. Each strategy goal made is a top-down approach, meaning that the strategy goals are made based on the approach of vision, mission, external and external conditions. The strategy map has 4 (four) perspectives that must be considered and should not be reversed in order, starting from the financial perspective, customer perspective, internal business process perspective and learning perspective and growth. The policy-making process must be top-down from top to bottom, starting from the financial goal then decreasing to the next goal. While the reciprocal process flows from the bottom up. But before determining the selection of the type of corporate-level strategy or business unit strategy it is worth reviewing how the strategy appeared or was in shape. In forming a strategy, it must focus on the vision, mission, goals and objectives, so several methods and rules can be used in the formation of the strategy. In addition to SWOT, the analysis that is considered more effective is the Balance Scorecard (BSC) method. After the formation and planning of the strategy is carried out, the next step is the process of implementing the strategy or implementing the strategy